Повышение эффективности теплообменных аппаратов паротурбинных установок за счет применения профильных витых трубок (Известия высших учебных заведений: Проблемы энергетики)
The generalized data are presented on the effectiveness of twisted profile tubes (TPT) in steam turbine heat exchangers: condensers, feed water heaters, hot water heaters, oil coolers, general and auxiliary power station heat exchangers. The guaranteed value is specified of the effect of TPT application in specific steam turbine heat exchangers.